Inscrições de si: da porta de banheiro ao chat - Bordin, Dagoberto José (2005)
Writing pervades human history, from rupestrian inscriptions to internet. Although supports change – walls, papyrus, parchments, tiles, papers, computer monitors – there remains a register, which transports human being beyond its own existence and which, precisely, renders it existing. In this thesis, I argue that restroom graffiti, apocryphal and ephemeral by their nature, are a link of the chain that identifies human being as the one who is capable of writing. It is an entity that can be figured out through its marks. Without aiming to interpret inscriptions, I restrict myself to observing that a great amount of impressions prefer to be revealed on the subversive support of the cell defined by the restroom door. And that the freedom of being anonymous that characterizes that door is kept when its contents are transposed to internet chats